The Comparison of the Use of Directive Speech Acts in Bad Boys Ride or Die and Sri Asih Movies - Hans; Sugiharti, Dona Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research explores the differences in the use of directive speech acts between American and Indonesian cultures as represented in two culturally distinct films: Bad Boys: Ride or Die (2024) from the United States and Sri Asih (2022) from Indonesia. The study is focusing specifically comparison on the directive speech acts performed by the main characters in each movie. Using John Searle’s (1979) classification of directive speech acts; such as commanding, ordering, requesting, advising, suggesting, challenging, begging, and inviting, the research identifies and categorizes the types of directive speech acts, then compares how they are culturally expressed in the respective films. This research uses the qualitative method. The data were collected from both movie transcripts, where only the utterances performed by the main characters, which is Mike and Marcus in Bad Boys: Ride or Die, and Alana in Sri Asih were analyzed. The findings reveal that the American main characters tend to perform directives in a more direct, and assertive, reflecting the individualism, openness, and low-context communication. In contrast, the Indonesian main character often perform directives in a more indirect, polite, and hierarchical way, highlighting collectivist values and high-context communication norms. This study provides insights into how culture influences language use, particularly in directive speech acts. It emphasizes the comparison of two different cultures that can affect how American and Indonesian perform directive speech acts through the movie context. The findings not only contribute to the field of pragmatics but also offer practical implications for intercultural communication.